The effects of material properties on solute transport during entrapment of a bubble subject to horizontal solidification - Wei, P.S.; Lin, P.Y. (International communications in heat and mass transfer, 2022)
Solute transport in the presence of a pore resulting from an entrapped bubble during horizontal solidification of water containing carbon dioxide is numerically and parametrically investigated. Structural material containing pores degrade microstructure, whereas materials with pores can also be functionally used to enhance efficiencies of engineering, foods and biomedical industries, and control outcome of geophysics and global warming, etc. In this study, transport equations including mass, momentum, energy and concentration transport equations satisfied by their interfacial balances between liquid, gas pore, and solid were solved with the COMSOL commercial computer code. Extending previous work dealing with influence of fluid flow, the present results further find that the effects of metallurgical and thermal properties on solute transport processes during entrapment of a bubble. Decreases in Henry's law constant, partition coefficient and liquid solute diffusivity, and increases in solid thermal conductivity increase solute concentration in solid around an entrapped pore. Predicted contact angle during solidification is in good accordance with computed analytical results confirmed by measured data. The findings of this study can help for better understanding of pore formation in the solid during horizontal solidification.